2010
DOI: 10.1021/ic1002012
|View full text |Cite
|
Sign up to set email alerts
|

Orientation and Stereodynamic Paths of Planar Monodentate Ligands in Square Planar Nickel N2S Complexes

Abstract: The well-established presence of histidine donors in binding sites of Ni-containing biomolecules prompts the study of orientational preference and stereodynamic nature of flat monodentate ligands (L = imidazoles, pyridine and an N-heterocyclic carbene) bound to planar N 2 SNi moieties. Square planar [N 2 SNiL] n+ complexes are accessed through bridge-splitting reactions of dimeric, thiolate-S bridged [N 2 SNi] 2 complexes. The solid state molecular structures of three mononuclear products, and three monothiola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 69 publications
(175 reference statements)
1
25
0
Order By: Relevance
“…These data are consistent with the structural models depicted in Scheme 1; at pH 7.4, the data is consistent with each peptide containing two mononuclear nickel sites that collapses into a binuclear cysteinate bridged Ni 2 center at high pH, the formation of which is well represented in small molecule Ni-thiolate chemistry [47,48]. two mononuclear nickel sites that collapses into a binuclear cysteinate bridged Ni2 center at high pH, the formation of which is well represented in small molecule Ni-thiolate chemistry [47,48].…”
Section: Nickel K-edge X-ray Absorption Spectroscopysupporting
confidence: 86%
See 2 more Smart Citations
“…These data are consistent with the structural models depicted in Scheme 1; at pH 7.4, the data is consistent with each peptide containing two mononuclear nickel sites that collapses into a binuclear cysteinate bridged Ni 2 center at high pH, the formation of which is well represented in small molecule Ni-thiolate chemistry [47,48]. two mononuclear nickel sites that collapses into a binuclear cysteinate bridged Ni2 center at high pH, the formation of which is well represented in small molecule Ni-thiolate chemistry [47,48].…”
Section: Nickel K-edge X-ray Absorption Spectroscopysupporting
confidence: 86%
“…Nickel thiolates are susceptible to oxidative damage by O 2 and H 2 O 2 [52,53], yet the NiSOD active-site is robust against oxidative damage effected by such species. Possible explanations for protection of the NiSOD active-site against Ni-S oxidative damage by ROSs have been proposed, including electronic fine tuning of the Ni-S moiety via the mixed amine/amide coordination environment [54,55] and a fast rate of the O 2 − disproportionation reaction relative to the rate of oxidation of the coordinate cysteinate sulfur atoms [45,48,49]. In this study we have shown that oxidation of the Ni-S-Cys bond by O 2 is slow for {Ni 2 (SOD mds )} at pH = 7.4, with a half-life of nearly 7 h under the reaction conditions investigated (ambient O 2 concentration, 1.0 mM {Ni 2 (SOD mds )}).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The weak band at about 600 nm in the visible region of the spectrum, which is so characteristic of tetrahedral and octahedral complexes,28 indicates symmetry distortion effect that causes deviation from planarity due to chiral distortion29–31 that lead to lack of both plane of symmetry and inversion center. It can be assigned to the weakest energy transition of d xy → d italicx 2italicy 2.…”
Section: Resultsmentioning
confidence: 99%
“…The simple dinickel buttery complex precursor may be split by various nucleophiles including carbenes, imidazoles, thiolates, and selenoates. [49][50][51] With the chalcogenates, entry to NiFe bimetallics is possible making use of the (h5-C 5 H 5 ) Fe(CO)(NCCH 3 ) 2 + receiver species outlined in Fig. 6.…”
Section: O-uptake In Complexes Related To [Nifes]-and [Nifese]-h 2 Asmentioning
confidence: 99%